Pustaka, Ruang Publik Dan Tindakan Komunikatif: Kajian Terhadap Perpustakaan Cahaya Ilmu Sma Negeri 1 Bengkulu Tengah - Adzkiyah Mubarokah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The theory proposed by Jurgen Habermas is that public spaces and communicative actions can be applied to the world of libraries, the Cahaya Ilmu library of SMAN 1 Bengkulu Tengah is one of the district-level school libraries that has adequate facilities as a public space. The purpose of this study was to see the relationship between communicative actions and public spaces reviewed at the Cahaya Ilmu library of SMAN 1 Bengkulu Tengah. This type of research uses a type of field research. As a result, the library can be said to be a public space whose activities require communicative actions that take place on the rules of the library rules that demand responsibility from several parties in accordance with mutually agreed agreements. library which is a public space open to anyone, where the Cahaya Ilmu library can be accessed by anyone either directly to the library or online, Cahaya Ilmu library activities are publicly funded through BOS funds and voluntary donations from the local community, access to information served to the public is satisfactory with various services and can be accessed as widely as possible and the Cahaya Ilmu library collaborates to expand the network  libraries both internally and externally.